Neointima Formation in Injured Hamster Carotid Artery Is Effectively Prevented by the Combination G4120 and Quinapril - Matsuno, Hiroyuki; Marie Stassen, Jean; Moons, Lieve; Vermylen, Jos; Hoylaerts, Marc F (Thrombosis and Haemostasis, 1996)
The prevention of neointima formation by the tissue selective angiotensin converting enzyme (ACE) inhibitor quinapril and by the combination quinapril/G4120 (a platelet αIIbβ3 and smooth muscle cell αvβ3 antagonist) was investigated in a hamster carotid artery injury model. Quinapril at 10 mg/kg/day reduced neointima formation by about 45%, 1 and 2 weeks after injury to the artery, i.e. significantly better than the non-tissue selective ACE inhibitor captopril at 100 mg/kg/day. Quinapril did not decrease the early smooth muscle cell (SMC) proliferation in the media, but in agreement with its inhibition of the carotid artery ACE activity by 62%, SMC proliferation was reduced by 70% in the newly forming intima. To improve the inhibition of early medial SMC proliferation, quinapril (10 mg/kg/day) was complemented with G4120 (100 Μg/kg/h). This combined treatment reduced the proliferation of medial SMCs to about 50% throughout the first week following injury, whereas intima SMC proliferation was reduced by 70% throughout treatment. Accordingly, the drug combination reduced neointima formation more potently than each drug separately by 70%. The disruption of medial elastic laminae, observed in the control and G4120 treated group, was consistently reduced when G4120 was complemented with quinapril. Thus, the present study shows in a hamster model of carotid artery injury, that combining drugs that prevent SMC migration and proliferation via different modes of action can lead to the effective prevention of neointima formation.